Persistent quacking in dabbling ducks: a predator-luring signal? - McKinney, Frank; Buitron, Deborah; Derrickson, Scott R (Wildfowl, 1990)
Female dabbling ducks of many species give bouts of loud, monotonous quacks during the prelaying period. From their characteristics, and the situations in which they are given, these calls do not appear to be directed towards the mate or other conspecifics. Persistent quacking is closely associated with nest-site prospecting and it can be triggered by various stimuli, including the appearance of potentially dangerous predators. We suggest that this vocalization is designed to attract the attention of mammalian predators, causing them to betray their presence. The information obtained could be valuable to females in enabling them to select safe nest-sites.